Rancang Bangun Alat Penyimpanan ASI Dilengkapi Indikator Kadaluarsa Berbasis Arduino Uno - Risnawaty Alyah; St. Fatimang Fatimang (Lontara Journal of Health Science and Technology, 2021)
Breast milk storage is a tool used to store breast milk by cooling it using a certain temperature. Its function is to maintain the durability of breast milk so that the content in breast milk remains stable. Breast milk heater is a device that is used to warm breast milk by heating it to the temperature of the human body in general. Its function is to warm breast milk when it is cooled. Breast milk storage has a storage time of 24 hours with a temperature of 15°C, while the heating process uses a temperature of 37°C according to the temperature of the human body in general. In this research, the module uses the LM35 sensor as a hot room temperature sensor and a cold room temperature sensor. The temperature measurement detected by the LM35 is measured using a thermometer. The temperature data was taken 6 times. Based on the results of the analysis of measurements on breast milk storage at a temperature of 15°C, it has a standard deviation of 0.148, an error of 1.33% and an uncertainty of 0.013. And the results of the measurement analysis on heating breast milk with a temperature of 37°C have a standard deviation of 0.034, an error of -0.27% and an uncertainty of 0.06.